Webster's third new international dictionary of the English language, unabridged / Since 1847 the Ultimate Word Authority for Schools, Libraries, Courts, Homes, and Offices - Gove, Philip Babcock (Edt)/ Gove, Philop Babcock (Edt)/ Merriam-Webster, Inc (Cor); Gove, Philip Babcock, 1902-1972.; Merriam-Webster, Inc. (Springfield, Mass. : Merriam-Webster, 1993)
Nearly half a million entries provide standard and variant pronunciations, etymologies, comprehensive definitions, updated usage illustrations, and synonym articles.
Keywords: English language -- Dictionaries